Trump and Modi: Seeking a Global Partnership? - Ladwig III, Walter C (2017)
The visit of the Indian Prime Minister to Washington DC provides an opportunity for the US and India to set aside some of the uncertainties that have set into the relationship. President Trump and Prime Minister Modi must be ambitious and spell out a vision befitting a global partnership.